2022
DOI: 10.3390/antiox11050945
|View full text |Cite
|
Sign up to set email alerts
|

Zeolitic Imidazolate Framework-8 Nanoparticles Exhibit More Severe Toxicity to the Embryo/Larvae of Zebrafish (Danio rerio) When Co-Exposed with Cetylpyridinium Chloride

Abstract: The combined application of nanoparticles and surfactants has attracted tremendous attention in basic research and industry. However, knowledge of their combined toxicity remains scarce. In this study, we exposed zebrafish embryos to cetylpyridinium chloride (CPC, a cationic surfactant, at 0 and 20 μg/L), zeolitic imidazolate framework nanoparticles (ZIF-NPs, at 0, 30, and 60 mg/L), and their mixtures until 120 h post-fertilization (hpf). Within the used concentration range, both single and combined exposures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…Remarkably, a number of reports from other authors linked hyperactivity either to exposure to antioxidants or to upregulation of antioxidant gene expression [22][23][24][25][26][27]. In line with this evidence, the hyperactivity observed in CM-treated larvae strictly associates with a reinforced antioxidant performance at the epigenetic and transcription level, as well as in the overall value of their antioxidant capacity.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Remarkably, a number of reports from other authors linked hyperactivity either to exposure to antioxidants or to upregulation of antioxidant gene expression [22][23][24][25][26][27]. In line with this evidence, the hyperactivity observed in CM-treated larvae strictly associates with a reinforced antioxidant performance at the epigenetic and transcription level, as well as in the overall value of their antioxidant capacity.…”
Section: Discussionsupporting
confidence: 59%
“…According to the literature, the behavioural effects we observed following CM exposure might be attributed either to the downregulation of the brain-derived neurotrophic factor (bdnf ) gene [19][20][21] or to the overexpression of genes involved in redox homeostasis [22][23][24][25][26][27].…”
Section: Exposure Impacts On the Antioxidant Gene Networkmentioning
confidence: 95%
“…Several recent studies have suggested that the behavioral toxicity of ZIF-8 NPs to zebrafish larvae is strongly affected by their exposure concentration and duration. For example, Hu et al [15] have reported that ZIF-8 NPs (50-200 mg L −1 for 6 days) could significantly decrease the swimming speed of zebrafish larvae in a dose-dependent manner, Shi et al [34] have reported that embryonic exposure to ZIF-8 NPs (9.0 mg L −1 for 5 days) significantly increased the locomotor activity of newly hatched zebrafish larvae, and Qiu et al [33] have reported that embryonic exposure to ZIF-8 NPs (0.3 and 0.6 mg L −1 for 5 days) did not significantly alter the locomotor activity of zebrafish larvae. Furthermore, except for nontoxicity (i.e., nanosize effects), ZIF-8 NPs can also induce toxic effects by releasing Zn ions into exposure mediums [9,17,49].…”
Section: Discussionmentioning
confidence: 99%
“…The zeolitic imidazolate framework-8 nanoparticles (ZIF-8 NPs) were produced via the mechanochemical reaction [32] between ZnO and 2-methylimidazole (J&K Scientific LLC, San Jose, CA, USA) with a molar ratio of 1:2 and particle sizes of 100-400 nm [33]. Other chemical reagents (analytical grade) were purchased from Sinopharm Chemical Reagent Co., Ltd. (Shanghai, China).…”
Section: Chemicalsmentioning
confidence: 99%
“…4,5 To date, various applications of MOFs have been researched, including but not limited to CO 2 capture, 6,7 catalysis/photocatalysis, 8–10 adsorption, 11 drug delivery, 12–14 electrochemistry, 15–17 fluorescent detection 18,19 and so on. 20–23 Many researchers once focused on MOFs with morphologies of 0D particles and 1D nanorods/nanowires. 24 Recently, increasing efforts have been devoted to 2D MOFs due to their large potential in catalysis, separation and sensing.…”
mentioning
confidence: 99%